El gaucho rioplatense del siglo XIX y las primeras décadas del XX: una tipología desde la historia y la literatura - Caballero, Blanca Álvarez (Diálogos Latinoamericanos, 2015)
In this article I put forward a historical-literary typology of the gaucho rioplatense. I focus on two fundamental moments in the history of the gaucho: the first one, ranging from the late 18th century (with the official historical-literary emergence of the gaucho) until the last third of the 19th century, with the disappearance of the legendary wandering gaucho bravo due to the ongoing modernization process. In the second moment the gaucho becomes either a paid employee in the ranch, or a hunter outside the limits of the ranch, or a ”compadrito”. I will analyze the gaucho –in particular, the gaucho found in poetry- in his particular social environment which included diverse human races, an aspect which shaped his personality.